Gender Differences in Achievement, Behavior, and STEM Interest Among Learners Using Minecraft - Esclamado, Maricel A. (Archīum Ateneo, 2024)
In this paper, we analyze how male and female learners differ in their in-game behaviors, knowledge assessment outcomes, and STEM interest using the What-If Hypothetical Implementations using Minecraft (WHIMC). We also investigate how male and female learners’ self-reported levels of frustration and boredom relate to these outcomes. We examine in-game data, out-of-game assessment data, self-reported frustration and boredom, and results of the STEM interest questionnaire (SIQ) from 175 Grade 8 learners from a school in the Philippines. We found that male learners tend to explore more than female learners. Both genders learn more through more exploration, making more observations, and completing tasks, but only female learners benefit from having more idle time. Male learners had a higher increase in STEM interest compared to female learners, while there is no significant difference in assessment scores between the genders. This study also found that boredom and frustration have a negative impact on academic outcomes, behavior, and STEM interest, especially among female learners. Bored female learners tend to do less well on post-game assessments, explore less, and make fewer observations. Frustrated female learners tend to not complete the task. Female learners who expressed frustration or boredom tend to have a decreased interest in SIQ in the Interest category after playing WHIMC.